El contramovimiento evangélico conservador en el Perú (2009-2019): aliados, recursos y estrategia - Tello Aguinaga, Kevin (2024)
The fight against LGBT rights and the gender approach in Peru has been led mainly by the conservative evangelical countermovement, made up of evangelical churches, organisations and actors. This article identifies the main allies of the countermovement and analyses the countermovement's relationship with each of them. It argues that the backing of conservative members of Congress, the alliance with the Catholic Church and the support of transnational pro-life and pro-family networks provided a series of institutional, political, organisational and economic resources that increased the countermovement's chances of success and enabled it to mobilise in different arenas and at different levels. It was found that conservative members of Congress used their legislative powers and prerogatives to stop or reverse pro-LGBT rights initiatives in Congress, and their political capital to make visible and legitimise the countermovement's demands. For its part, the Catholic Church used its political influence to try to change public policy and public opinion, and coined the term "gender ideology", which was used by the countermovement to successfully frame its campaign against the gender approach. Finally, the transnational pro-life and pro-family networks sent political operators, created meeting and coordination spaces at the regional level, transmitted knowledge, socialised experiences and financed the local conservative agenda. The research is based on an exhaustive review of secondary data sources that was complemented by interviews with key actors.